2006
DOI: 10.1111/j.1365-2044.2006.04643.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four airway training manikins as simulators for inserting the LMA Classic*

Abstract: Summary Airway manikins have traditionally been used for teaching mask ventilation and tracheal intubation. There is an increasing need to use manikins for training in procedures such as insertion of the laryngeal mask airway. We have assessed four new airway training manikins (latest versions of the Airway Trainer™ (Laerdal, Norway), Airway Management Trainer™(Ambu, UK), ‘Bill 1’™(VBM, Germany) and Airsim™(Trucorp, Ireland)) as simulators for insertion of the LMA Classic™ laryngeal mask airway. Twenty volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 6 publications
1
29
1
2
Order By: Relevance
“…A recent abstract reported the i-gel to be better than the LMA-Classic . It is quite possible that this was due to differences in ease of insertion of the device into a manikin as the i-gel is much easier to insert in a manikin than the cLMA [24,25]. Further work, in patients, would be welcome.…”
Section: Discussionmentioning
confidence: 99%
“…A recent abstract reported the i-gel to be better than the LMA-Classic . It is quite possible that this was due to differences in ease of insertion of the device into a manikin as the i-gel is much easier to insert in a manikin than the cLMA [24,25]. Further work, in patients, would be welcome.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rigid plastics, the lack of collapsible soft tissues, absence of secretions and the fact many manikins do not have anatomically correct epiglottic and laryngeal structures makes them very unlikely to be useful surrogates for evaluation of either easy or difficult intubation. We recently evaluated four modern manikin in several domains of airway management [30][31][32]. In each of the studies we observed that the manikins failed to mimic the 'softer' aspects of airway management: even when procedures (such as device insertion) were possible, they were only infrequently considered 'lifelike'.…”
Section: Discussionmentioning
confidence: 99%
“…It is often used to measure respondents' attitudes by asking the extent to which they agree or disagree with a particular question or statement. The concept of lifelikeness has been used previously to compare manikins with real patients [12]. The volunteers were also asked if the simulator model was more life-like for lumbar puncture or epidural insertion; any other comments, were recorded as free text.…”
Section: Methodsmentioning
confidence: 99%